Role of Psychological Wellbeing in Mediating Impact of Worklife Integration to Organization Commitment - Hapsari, Ignatia Aditya (Bina Nusantara University, 2025)
This research aim to investigate impact Work to Life Integration (WLI) to Organization Commitment (OC) for remote working employee who works in Jabodetabek, Indonesia, and how role of Psychological Wellbeing (PWB) increasing this impact. Due to trend of flexible working arrangement during Covid 19 pandemic and development of technologies that can facilitate it, there are still few references relate to work to life integration’s impacts. In this study researcher choose to investigate its impact to organization commitment which matters for employers. This research is a quantitative study using online survey to 400 employees and used SEM PLS to get the result. Result of the study found that WLI has significant impact to OC and WLI has significant impact to OC through PWB as a mediator, but apparently indirect impact of WLI to OC mediated by PWB is lesser than direct of WLI to OC.